2019
DOI: 10.1111/coa.13296
|View full text |Cite
|
Sign up to set email alerts
|

Association study of cell cycle proteins and human papillomavirus in laryngeal cancer in Chinese population

Abstract: Objective To investigate the role of human papillomavirus (HPV) in laryngeal squamous cell carcinoma (LSCC) and analyse the relationship between HPV and the expression of cell cycle‐related proteins. Design The study consisted of LSCC between 2005 and 2011 in Tongren Hospital. Clinical data such as age, sex, smoking/alcohol consumption, and TNM stage were collected. HPV DNA and cell cycle‐related proteins were assessed in terms of clinical features. Setting Single‐centre study. Participants A total of 332 LSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…50,51 In our series, this association between the HPV status and p53 expression was not found consistent with other studies. 52,53 On the other hand, the association between p16 expression and the presence of HPV DNA was not found in the laryngeal tumors of our series, which is in agreement with results already published. 54 Moreover, this relationship has not been detected in the study of the relationship between the HPV transcriptional activity and the p16 expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…50,51 In our series, this association between the HPV status and p53 expression was not found consistent with other studies. 52,53 On the other hand, the association between p16 expression and the presence of HPV DNA was not found in the laryngeal tumors of our series, which is in agreement with results already published. 54 Moreover, this relationship has not been detected in the study of the relationship between the HPV transcriptional activity and the p16 expression.…”
Section: Discussionsupporting
confidence: 93%
“…50,51 In our series, this association between the HPV status and p53 expression was not found consistent with other studies. 52,53…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signalling pathway has a vital function in LSCC by suppressing cell death (Chrysovergis et al, 2019;Yang et al, 2019). P53, a tumour suppressor factor, initiates DNA repair, cell cycle arrest and apoptosis and reacts to various kinds of cancer therapies (Cui, Qu & Liu, 2019;Ragos et al, 2018). The changes above are connected with the findings in this study that the BPs of the DEGs necessarily contribute to the progression of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Since HPV requires the host cell DNA replication machinery for its progeny production, the virus must ensure that the S-phase of the cell cycle continues, and to do so, several key molecules suffer alteration, which is a fact in the role of HPV in cervical cancer development. In nonanogenital HPV-related tumors, such as head and neck cancers (HNC), it was already observed that cyclin-dependent kinase inhibitors (CKI) p16 and p21 are two of the disrupted factors [7,8] together with the proliferating cell nuclear antigen (PCNA) in order to keep the cell in constant proliferation [9].…”
Section: Introductionmentioning
confidence: 99%